Implementasi Kemampuan Berbahasa Melalui Kegiatan Bermain Peran Dalam Menumbuhkan Karakter Anak Usia Dini - Budiarti, Erna; Fitriani (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2024)
This research aims to explore the implementation of language skills in children aged 5-6 years through role-playing activities as a strategy for forming character at an early age. The focus of the research involves analyzing the positive impact of role-playing activities on the development of children's language skills and character. This research is a type of qualitative descriptive research with a case study approach which specifically occurred at the Pelita Hati Kindergarten, Dusun Pulau Jelmu, sub-district. Jujuhan, district. Bungo, Jambi province. The research method involves observing children's participation in role-playing activities as well as qualitative analysis of changes in their character and language skills. The research results show that role-playing activities can effectively improve the language skills of children aged 5-6 years. Active participation in a variety of roles provides opportunities for children to develop vocabulary, understand sentence structure, and improve their communication skills. Apart from that, this activity also plays a role in shaping children's character, such as cooperation, empathy and creativity. These findings provide important implications for the development of early childhood education, by emphasizing the importance of integrating role-playing activities in the curriculum. Educators and parents can use this approach as a means to not only improve children's language skills, but also form positive characters from an early age. Thus, the implementation of role-playing activities can be an integral part of a learning strategy that is holistic and oriented towards children's personal development.